EXAMINING THE FACTORS AFFECTING THE SELECTION OF SUSTAINABLE TRANSPORT MODE IN INTERNATIONAL TRADE (Third Sector Social Economic Review, 2024)
Sustainability enables economic development to be supported and the ecosystem to be strengthened by using existing resources correctly. It ensures the continuity of activities by keeping sustainability, environmental awareness, economic awareness and social awareness factors in play while contributing to the development of these elements. Transportation activities include the process of transferring both goods and living objects from one place to another, which has been going on since the existence of humanity. Today, many economic, social and environmental factors have to be taken into consideration during the transportation activities. The choice of transportation mode in international trade is one of the most important issues that enable businesses to stand out in many important aspects, especially competitive advantage, cost advantage, flexibility, operational efficiency and effectiveness. The choice of transportation mode in international trade is one of the most significant issues that enable businesses to stand out in many important aspects, especially competitive advantage, cost advantage, flexibility, operational efficiency and effectiveness. In this study, the elements affecting the selection of sustainable transportation mode in global alternate have been tested the use of DEMATEL and SWARA methods, which might be multi-standards choice making (MCDM) techniques. While carrying out this review, the relevant literature was scanned and expert opinions were used. 10 main criteria that are effective in transport mode selection were determined and six experts were interviewed. As a end result of the research, it become visible that the maximum tremendous criterion in deciding on a transportation mode is the price criterion. It has been observed that the least important criterion in transportation mode selection is green operations. Although selecting a sustainable transportation mode in global alternate is a strategic decision, it's miles idea that figuring out the order of significance of the standards will offer massive blessings to enterprise representatives and researchers of their work.
Keywords: International trade; Transport mode selection; Sustainability; Multi-Criteria Decision Making; Sustainable transport